2015
DOI: 10.1007/s13277-015-3653-2
|View full text |Cite|
|
Sign up to set email alerts
|

Exon 19 deletion of epidermal growth factor receptor is associated with prolonged survival in brain metastases from non-small-cell lung cancer

Abstract: Brain metastasis (BM) is a poor prognostic factor for non-small-cell lung cancer (NSCLC). Recent studies have shown that oral epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) were effective for BM from NSCLC with EGFR mutation. However, the relationship between EGFR mutations and prognosis of NSCLC BM patients remains to be determined. In this study, we investigated the impact of EGFR mutation status on the survival of BM patients from NSCLC. One hundred six patients with BM from NSCLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
3
7
0
Order By: Relevance
“…We supposed that may due to clinically more younger patients are tend to receive EGFR-TKIs alone because of the intolerance of potential side-effect of brain RT on the nervous system. Moreover, we found that patients with 19deletion achieved a significant improved OS than patients with 21 L858R after the combination therapy, which was consistence with previous study that 19deletion was a favorable prognosis factor for NSCLC patients with BM (44).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We supposed that may due to clinically more younger patients are tend to receive EGFR-TKIs alone because of the intolerance of potential side-effect of brain RT on the nervous system. Moreover, we found that patients with 19deletion achieved a significant improved OS than patients with 21 L858R after the combination therapy, which was consistence with previous study that 19deletion was a favorable prognosis factor for NSCLC patients with BM (44).…”
Section: Discussionsupporting
confidence: 91%
“…for the patients with exon 19 deletions, there was no significant difference in PFS between the high and low plasma concentration groups (median survival: 12.0 vs. 17.0 months, P=0.9548), In contrast, the iPFS of 21 L858R mutated patients was significantly different between low and high concentrations of gefitinib (median survival: 8.0 vs. 16.0 months, P<0.05) (41), which indicated that iPFS in patients with exon 21 mutation relied more on concentration than 19deletion patients; and since combined WBRT was associated with elevated CSF concentration of EGFR-TKIs by breaking BBB, both of them seem to partly explain why exon 21 mutation favors combined therapy. Moreover, several previous studies demonstrated that exon 19 and 21 mutations had different response to gefitinib or erlotinib, and patients with exon 19 deletion had longer progression-free survival than those with exon 21 L858R mutation when treated with EGFR-TKIs (42)(43)(44). This may explain the difference of additional value of brain RT as a complement to EGFR-TKIs.…”
Section: Discussionmentioning
confidence: 96%
“…Other studies found molecular profile to be an independent prognostic factor for patients with NSCLC BM. Li et al noted that EGFR exon 19 deletions were associated with a better prognosis ( p = 0.034) in a population of 106 patients with BM from NSCLC [31]. These results are consistent with ours and suggest that EGFR mutations remain a good prognostic factor even if they are associated with a higher rate of BM relapse after local treatment.…”
Section: Discussionsupporting
confidence: 90%
“…Of the 18 included studies (encompassing a total of 4373 NSCLC patients with brain metastases), 3 had a prospective design [18, 26, 30] and 15 had a retrospective design [14–17, 1925, 2729, 31]. Nine included studies were from Asia [14, 15, 17, 18, 20, 2426, 31], and 9 were from Europe or America [16, 19, 2123, 2730].…”
Section: Resultsmentioning
confidence: 99%